The Effect of Organizational Behavior on Experience-Based Strategies at Cafe Utton - Asnia Minarti; Nur Alisyah; Ratih Pratidina; Puji Rahmah; Surianti Surianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to analyze the influence of organizational behavior on experience-based strategy at Café Utton. In the current competitive business environment, cafés are required not only to offer products and services but also to create meaningful customer experiences. Organizational behavior plays an important role in shaping employee attitudes, communication patterns, teamwork, and service quality, which ultimately contribute to the implementation of an effective experience-based strategy. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees and customers of Café Utton. The variables in this study consist of organizational behavior as the independent variable and experience-based strategy as the dependent variable. Data analysis was conducted using statistical techniques to determine the relationship and influence between variables. The results of the study indicate that organizational behavior has a positive and significant effect on experience-based strategy at Café Utton. This shows that better organizational behavior within the workplace leads to improved customer experience, which strengthens customer satisfaction and loyalty. Therefore, organizational behavior is an important factor in supporting the successful implementation of experience-based strategies in the café industry